(untitled) (Jahangirnagar University Journal of Biological Sciences, 2021)
Nowadays, the use of spices and other herbs have extensively increased due to their medicinal values all over the world. However, the monitoring of heavy metal contamination in spices has also been increased in recent years. A study has been conducted to determine the concentration of eight heavy metals such as Lead (Pb), Cadmium (Cd), Chromium (Cr), Arsenic (As), Zinc (Zn), Iron (Fe), Copper (Cu) and Manganese (Mn) in mainly three different types of turmeric samples (Curcuma longa). The turmeric samples analyzed were (i) Unpacked bulk powder available at three different local markets in Dhaka (ii) Packed and marketed by three branded companies, and (iii) Raw turmeric directly collected from different local farmlands. The samples were analyzed using Atomic Absorption Spectroscopy (AAS). The concentration of most of the heavy metals were found within the limit recommended by WHO (6.0000 ppm) except lead (12.3469 ppm) in unpacked-3 bulk sample. This study also showed the concentration of heavy metals were present in a lower amount in packed power samples compared to unpacked bulk powder samples. The result of this analysis would be helpful for public awareness in consumption of different spices. The concerned authorities who are responsible for monitoring and regulating the food chain in the market in our country may also get a great message about heavy metal contamination of spices. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 13-20, 2020 (June & December)